Politik Pendidikan: Studi Kasus Formulasi Kebijakan Alokasi 20 Persen APBN Untuk Pendidikan - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Andhyka Muttaqin (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2010)
This research stems from the emergence of an issue about 20 percent of the budget for education, followed by the Constitutional Court Decision No. 026/PUU-III/2005 dated March 22, 2006 which states for the education budget has not yet reached 20 percent as specified in the 1945 Constitution, the budget will always be against the Constitution in 1945. Researchers trying to come up how the trip actually 20 per cent allocation policy formulation national budget for education and political dynamics that exist therein. As the basis is the fourth amendment to the 1945 Constitution article 31 paragraph (4) which states "The state prioritizes the education budget of at least twenty percent of budget revenues and expenditures of state and local spending and revenue budget to meet the needs of national education" is derived to be a Law No. 20 Year 2003 on National Education System of article 49 paragraph (1) that "education fund in addition to salaries for teachers and education costs a minimum of 20 percent is allocated for official from the State Budget (APBN) in the education sector and at least 20 percent of Local Government Revenues and Expenditures (budget) ". The purpose of this study was to describe and analyze the travel policy formulation 20 percent budget allocation for education and to know the political dynamics that occur during the formulation process.